2022
DOI: 10.3390/agriculture12040534
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion in Ryegrass-Fescue Hay by Pleurotus ostreatus to Increase Their Nutritional Value for Ruminant

Abstract: Carbohydrates from lignocellulosic feed can be released by basidiomycete fungi for ruminal fermentation. This study aimed to evaluate the bioconversion of hay of ryegrass-fescue (Lolium perenne—Festuca arundinácea) by solid state fermentation with Pleurotus ostreatus, to obtain superior quality hay. After only 14 days of fermentation, crude protein (CP) (4.73 to 5.16%), and non-fibrous carbohydrates (NFC) (20.84 to 25.04%) increased, while neutral detergent fiber (NDF) (68.72 to 64.87%) and acid detergent lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The CP values of feed were comparable to the findings of Marino et al [ 28 ] and Mhlongo et al [ 15 ], yet higher than those reported by Nasiri et al [ 29 ] and Yousefi [ 30 ], and lower than in Mahfuz et al [ 31 ]. The obtained NDF and ADF values were higher than the findings of Kalvandi et al [ 10 ], Dilfy et al [ 32 ], and Yousefi et al [ 33 ], and lower than those of Astudillo-Neira et al [ 34 ]. Fazaeli and Masoodi [ 35 ] reported an increase in crude protein and ash in oyster mushroom-cultivated substrate.…”
Section: Resultscontrasting
confidence: 75%
“…The CP values of feed were comparable to the findings of Marino et al [ 28 ] and Mhlongo et al [ 15 ], yet higher than those reported by Nasiri et al [ 29 ] and Yousefi [ 30 ], and lower than in Mahfuz et al [ 31 ]. The obtained NDF and ADF values were higher than the findings of Kalvandi et al [ 10 ], Dilfy et al [ 32 ], and Yousefi et al [ 33 ], and lower than those of Astudillo-Neira et al [ 34 ]. Fazaeli and Masoodi [ 35 ] reported an increase in crude protein and ash in oyster mushroom-cultivated substrate.…”
Section: Resultscontrasting
confidence: 75%
“…The results showed that the conversion rates of cellulose and hemicellulose were 19.64 and 10.88%, respectively. Astudillo-Neira et al (2022) reported that carbohydrates from lignocellulosic feed can be released by fungi for fermentation. Datsomor et al (2022) reported that the P. ostreatus treated straw had a lower lignin content (3.3%) compared to the P. chrysosporium (6.2%) with the raw straw recording the 8.2% lignin fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Although not evaluated in the present study, the increase in SFCAs and ME with the microalgae is possibly due to a greater activity of the fibrolytic bacteria [ 10 ] and an increase in the production of propionate, while in the cases where it decreased, it is attributed to the reduction in other SCFA such as acetate [ 48 ]. Meanwhile, the calculated variations in CH 4 per unit of SCFA, ME, and OM may reflect the effects on DMD and SCFA, related to the composition and degradability of feed carbohydrates [ 77 ].…”
Section: Discussionmentioning
confidence: 99%